Case study of Bou-saada City, A Integrating the Analytical Hierarchy Process (AHP) and GIS to assess threats from oasis urbanization. Case study of Bou-saada City, Algeria. - Ameur Melki; Ali Redjem; Lahcene Hadj Hafsi (International Journal of Computational and Experimental Science and Engineering, 2026)
Urbanization’s growing threat to oases’ delicate and vital ecosystems, particularly in arid and semi-arid environments, demands immediate attention. These oases, essential to biodiversity, water resources, and indigenous inhabitants’ means of subsistence in Algeria, are increasingly threatened by urbanization and climate change. To assess the threats caused by urbanization in oasis ecosystems while taking into account local characteristics and sustainability issues, a geographic information system (GIS) was combined with a hierarchical analytical process (AHP) to analyze several criteria, such as distance to agricultural areas, sands, settlements, valleys, and roads, land uses, and slope. The Analytical Hierarchy Process (AHP) was applied to determine the importance weights of each criterion. A simple additive weighting method was used to assess spatial suitability for urbanization within the study area. Each criterion was evaluated using AHP and mapped using GIS. The resulting land suitability was reported on a scale of 0 to 10, respectively, from least to most suitable sites for urbanization. The study revealed that physical factors significantly influence the deterioration of the oasis and have determined the direction and scale of urban development. As a result, 73.39 km2 of the study area is identified as the most suitable for urbanization, 91.64 km2 moderately suitable, and 50.51 km2 unsuitable.